Teaching human evolution: How a museum programme in the palaeosciences improved learner performance - Grizelda van Wyk; Shaw Badenhorst (South African Journal of Science)
The teaching of evolution at school level in South Africa was introduced in 2006. However, evolution remains a controversial aspect for school learners in South Africa, and many misconceptions persist among teachers and learners. The study described in this paper sought to investigate whether an interactive palaeosciences university-based museum programme (PUMP) would benefit the examination outcome of learners in human evolution in the Gauteng Province of South Africa. The PUMP made use of sociocultural theory and consisted of inquiry-based activities with casts of hominin skulls and pelvic bones. The Cultural-Historical Activity Theory (CHAT) framework was used as a theoretical framework. Pre- and post-tests were written, before and directly after the activities, and a provincial examination essay question was analysed to see if there was a difference in results between those who attended the PUMP and those who did not. Focus interviews were conducted with learners and teachers. The results of this study indicate that the understanding of human evolution increased following PUMP. This study advocates an inquiry-based approach to the teaching of evolution to learners, preferably at an informal science learning institution such as a museum.